PERAN PEMUKA AGAMA DALAM INTERNALISASI NILAI-NILAI RELIGIUS PADA KEBUDAYAAN MASYARAKAT MODERN - Yudi Apriansyah; Rany Claudia; Syahwa Sestika; Rehan Okta Ade Pio (Universitas Pendidikan Ganesha, 2025)
Advances in technology and information have brought about changes in modern society. Modern society can change perspectives and blur religious values that were previously believed. Religious leaders play a crucial role in internalising religious values within modern society. This study examines the role of religious leaders from the perspective of strategies and challenges in internalising religious values. The study participants were religious leaders from Protestant, Catholic, Hindu, Buddhist, and Islamic faiths, totaling ten informants. This research employs a case study approach. The results of this study indicate that the religious values internalised in modern society have the meaning of love for God, humanity, and nature, manifested in strong compassion and tolerance. The role of religious leaders is crucial as intermediaries through strategies that begin with themselves, serving as good examples in society and adopting more humanistic approaches towards modern society. In addition, religious leaders utilise social media such as YouTube to convey religious values. Efforts to maximise the role of religious leaders face challenges, including the fact that modern society has its own set of values that sometimes do not align with religious teachings, prioritising materialistic aspects and wealth as the result of hard work, leading to a lack of belief in God